Avaliação da prevalência de diarréia em pacientes com HIV/Aids em serviço de referência em Belo Horizonte, 2007 - Odilia da Conceicao Custodio Vieira Lopes (2009)
INTRODUCTION: Diarrhea still remains as an important manifestation in HIV patients. The origin of diarrhea is multifactorial and can be grouped in: infectious, inflammatory, and secondary to antiretroviral therapy. HIV also leads to a progressive failure of physiological and immunological functions of the gastrointestinal tract, leading to malabsorption, weight loss and development of opportunistic infections. Despite the knowledge of its causes, data regarding the prevalence and factors associated with diarrhea after the introduction o HAART are scarce. OBJECTIVE: Assess the prevalence of diarrhea and its associated factors and evaluate themanagement given to HIV/Aids inpatients with diarrhea. PATIENTS & METHODS: Medical records of patients hospitalized with HIV/Aids during 2007 in Hospital Eduardo Menezes (Belo Horizonte, MG) were analyzed. 365 patients were included in the study. RESULTS: Age ranged from 18 to 78 years, with a mean of 40.63 years. 253 cases (69.3%) were men. Mean hospitalization time was 28.04 ± 1.72 days. During the hospitalizion, 55 (15.1%) deaths were observed. The main mode ofinfection was heterosexual sex transmission. 117 (32.05%) patients had diarrhea, of which 48 (41.03%) had chronic diarrhea. The main etiological agent was Cryptosporidium, seen in 12.0% of all cases. Adhesion to therapy and atazanavir were protecting factors for the development of diarrhea. Diarrhea led to longer hospitalization times. CONCLUSION: Diarrhea is an important cause of morbidity in patients with HIV. Diarrhea was associated with worse adherence to therapy.